Perceived Experience of Old Adult Patients with Services provided in the Tertiary Level Hospitals in Kathmandu: A Cross-Sectional study - Khatri, Pratima; Sharma, Muna; Singh, Shreejana (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Most old adults are vulnerable to multiple non-communicable diseases and need extensive care, treatment and support for a good quality of life. The main objective of this study was to identify the old adult patient’s perceived experience with the care provided in the tertiary level hospitals under the Institute of Medicine, Tribhuvan University, Kathmandu, Nepal. Methods: The cross-sectional study was conducted among 404 old adult patients admitted with non-communicable diseases in two tertiary levels University Hospitals in Kathmandu, Nepal. An interview schedule was conducted with hospitalized old adult patients to collect data using a consecutive sampling technique. Results: Most participants [208 (51.5%)] were from the age group of 60 to 69 years with a mean age (± SD) of 71.1 (± 9.7) years. One-fourth [103 (25.5%)] of them were financially independent. Two hundred thirty-three (57.7%) were admitted with a single diagnosis. Two hundred forty (59.4%) participants bore their hospital expenses with out-of-pocket payment, and 40.6% were covered by a third party payment. The majority of them (86.1%) had the experience of finding approachable health personnel in the hospital whereas 82.7% felt that the cost of treatment was higher than expected. 80.4% perceived that access to the hospital service (e.g. getting the outpatient tickets) was user-friendly. However, only 10.9% experienced follow-up visits user friendly. Conclusions: The hospitals where this research was done have a relatively high standard of care for old adult patients. Old adult-friendly health policy, physical environments of the hospital, and advocacy for them should further be considered in the tertiary level hospitals for the benefit of old adult patients.